Advances in Foot-and-Mouth Disease Virus Proteins Regulating Host Innate Immunity - Peng, Jiangling; Yi, Jiamin; Yang, Wenping; Ren, Jingjing; Wen, Yuan; Zheng, Haixue; Li, Dan (Frontiers in Microbiology, 2020)
Foot-and-mouth disease (FMD) is a highly contagious disease, which affects cloven-hoofed animals such as pigs, cattle and sheep. The disease is caused by foot-and-mouth disease virus (FMDV) which has a non-enveloped virion of icosahedral symmetry encapsulating a posi-tive-sense, single-stranded RNA genome of ~8.4 kb. During FMDV in-fection, it has obvious immunosuppressive effects to the host. In recent years, the study on the immunosuppressive mechanism of FMDV has become a hot topic. In addition, studies have shown that many FMDV proteins are involved in the regulation of host innate immunity and re-vealed the mechanisms by which FMDV proteins mediated host innate immunity. In this review, the advance in mechanisms of interaction be-tween FMDV proteins and host’s innate immunity are summarized to provide a reference for comprehensive understanding of FMDV patho-genesis and theoretical basis for FMD prevention and control.